An Approach for Realizing Hybrid Digital Twins Using Asset Administration Shells and Apache StreamPipes - Michael Jacoby; Branislav Jovicic; Ljiljana Stojanovic; Nenad Stojanović (Information, 2021)
Digital twins (DTs) are digital representations of assets, capturing their attributes and behavior. They are one of the cornerstones of Industry 4.0. Current DT standards are still under development, and so far, they typically allow for representing DTs only by attributes. Yet, knowledge about the behavior of assets is essential to properly control and interact with them, especially in the context of industrial production. This behavior is typically represented by multiple different models, making integration and orchestration within a DT difficult to manage. In this paper, we propose a new approach for hybrid DTs by intertwining different DT models. We also show how to realize this approach by combining the Fraunhofer Asset Administration Shell (AAS) Tools for Digital Twins (FAST) to create Industry 4.0-compliant DTs with Apache StreamPipes to implement and manage multiple DT models. Our prototype implementation is limited to a subset of the AAS metamodel and pull-based communication between FAST and an external Apache StreamPipes instance. Future work should provide full support for the AAS metamodel, publish/subscribe-based communication, and other execution environments as well as deployment strategies. We also present how this approach has been applied to a real-world use case in the steel production industry.